The opportunities of economic and legal cooperation between EU - Armenia within the framework of the BRI - Armen Ju. Ghazaryan; Liana Marukyan; Meline V. Abrahamyan; Meline A. Ayvazyan (OrdnungsPolitisches Portal (OPO), 2022)
The EU's relations with Armenia are based on the EU - Armenia Comprehensive and Enhanced Partnership Agreement (CEPA), which was signed on November 24, 2017, and entered into force on March 31, 2021. Within the framework of this agreement, the cooperation of the EU and Armenia in various spheres is envisaged. The EU's support, in particular for the development of democracy and political, economic and institutional stability, is very important for the Republic of Armenia. From an economic point of view, the EU is one of the most colossal donors providing financial aid and doing foreign investment, which is an important component both in promoting exports in general and especially in the high-tech sector. The article aims to present in detail the existing achievements in the field of economic and legal cooperation, the prospects and opportunities for deepening sectoral cooperation, taking into account the potential mutual economic benefits that the EU and Armenia could have within the framework of the Armenian North-South Road Corridor and the Belt and Road Initiative.
Keywords: 330; EU-Armenia cooperation; CEPA; Belt and Road Initiative; Armenian North-South Road